Lower ST-elevation myocardial infarction incidence during COVID-19 epidemic in Northern Europe. (1st November 2020) - Piuhola, Jarkko; Kerkelä, Risto; Laine, Mika; Andersen, Geir Øystein; Ērglis, Andrejs; Kumsārs, Indulis; Thuesen, Leif; Sinisalo, Juha; Niemelä, Matti; Junttila, M. Juhani
Abstract: We compared the ST elevation myocardial infarction (STEMI) incidence during COVID-19 pandemic (March 2020) to January–February 2020 and to same time period in earlier years 2017–2019 in five Nordic-Baltic tertiary centers. During 2017–2019, there were no marked differences in STEMI incidence between January, February and March. During 2020, there was an average drop of 32% in STEMI incidence in March. The isolation measures may decrease the risk for respiratory virus infection and contribute to the lower STEMI incidence and that we might benefit from firmer suggestions on hand hygiene and social distancing during flu season at least among high-risk individuals.